EFL Pre-service Teachers’ Open Internet Reading Processing and Its Implication for Teaching: A Guided Think-Aloud Study - Laeli , Anita Fatimatul; Setiawan, Slamet; Anam , Syafi’ul (Pedagogika, 2023)
The mixed-method study explores EFL pre-service teachers’ cognitive processes during open Internet reading in the teaching practice. The data were analyzed through t-test and think-aloud protocol (TAP). The quantitative findings indicated that the participants in the TAP group performed better in reading performance than the non-TAP’s. The qualitative results indicated that the TAP group applied their reading processing through problem identification, selection, and elaboration.